Tracked Changes. Glass-reinforced thermosetting plastics (GRP) pipes and fittings. Test methods to prove the design of locked socket-and-spigot joints, including double-socket joints, with elastomeric seals. (4th October 2021) - British Standards Institution
No abstract available